A cobalt-doped titanium dioxide photocatalyst, a preparation method and application thereof

CN117680125BActive Publication Date: 2026-10-16CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211055425.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-31
Publication Date
2026-10-16
Estimated Expiration
2042-08-31

AI Technical Summary

Technical Problem

但二氧化钛自身表面活性位点缺乏、电荷复合较快,限制了其效率的提高

Benefits of technology

[0024] Compared with the prior art, the advantages of the present invention are as follows:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117680125B_ABST
    Figure CN117680125B_ABST
Patent Text Reader

Abstract

The application discloses a kind of cobalt-doped titanium dioxide photocatalysts and its preparation method and application.Cobalt is highly dispersed in nanometer titanium dioxide in the form of atomic dispersion.During the growth of titanium dioxide lattice, introduce cobalt source, and induce its uniform distribution in the titanium dioxide lattice skeleton through subsequent processing, the synthesis method is simple, without introducing additional template agent or inducer.At the same time, the electronic and chemical structure of the doped atom can be directly controlled during synthesis;By introducing metal doping, the number of surface active sites is increased while the carrier density of the semiconductor itself is improved, and the light absorption performance can be controlled by using the doping level, which can overcome the problem of serious carrier recombination of single semiconductor titanium dioxide itself, and due to the increase of light absorption performance and active sites, the activity and stability of photocatalytic carbon dioxide reduction can be greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of photocatalysis technology, specifically relating to a cobalt-doped nano-titanium dioxide photocatalyst, its preparation method, and its application. Background Technology

[0002] With the rapid development of the economy and society, the excessive consumption of fossil fuels has generated a large amount of carbon dioxide emissions, further triggering a serious energy and environmental crisis. The capture, utilization, and storage of carbon dioxide has become a key issue for the sustainable development of human society. Photocatalytic carbon dioxide reduction utilizes electrons generated by semiconductor photocatalysts under photoexcitation to react with CO2, reducing it to its high-value-added compounds for resource utilization. The solar energy utilization efficiency of photocatalysis mainly depends on three steps: light absorption by the semiconductor, separation and migration of photogenerated charges, and surface reactions. However, the current efficiency of photocatalytic CO2 reduction is relatively low, making it difficult to meet application requirements. The key lies in the design and construction of conductor photocatalysts. Many materials, including conductors and semiconductors, have been found to possess CO2 reduction properties, such as pure metals (e.g., Au, Ag), metal oxides (e.g., CuO, TiO2), metal sulfides (e.g., MoS2), and carbon materials (e.g., g-C3N4). Typically, methods such as morphology control (core-shell, hollow, multi-hollow, etc.), heteroatom doping, defect introduction, and heteromaterial construction are used to control the electronic structure of the catalyst and create highly active catalytic centers, which can effectively improve the carbon dioxide reduction activity. For example, Shuhei Furukaw et al. from Kyoto University reported the use of self-assembled supramolecular polymer colloidal particles (Rh-CPP) and colloidal aerogels (Rh-SAG) of cubic octahedral metal-organic polyhedra (Rh-MOP) for photocatalytic CO2 reduction to lactic acid, with a yield approximately 12 times that of Rh-MOF (Rhodium-based metal-organic polyhedra assemblies for selective CO2 photoreduction. J. Am. Chem. Soc. 2022, DOI: 10.1021 / jacs.1c12631). Peng Zhou et al. from the University of Michigan studied how to design S-vacancies on atomically thin SnS2 layers to promote water splitting, and the CO2 photoreduction performance of the Vs-SnS2 sample was significantly better than that of the initial SnS2 sample (8.2 times). S vacancies facilitate the acceleration of water splitting half-reactions, thereby speeding up vacancy elimination / proton release and promoting CO2 reduction (Boosting water decomposition by sulfur vacancies for efficient CO2 photoreduction. Energy. Environ. Sci. 2022, DOI:10.1039 / D1EE03764A).

[0003] Among the most common semiconductor photocatalysts, titanium dioxide (TID) exhibits stable structure, excellent physicochemical properties, and a wide spectral response range, making it crucial for photocatalytic water splitting, pollutant degradation, and carbon dioxide reduction. However, the lack of active sites on the surface of titanium dioxide and its rapid charge recombination limit its efficiency. Furthermore, conventional synthesis methods have inherent limitations, failing to yield nano-titanium dioxide photocatalysts with high overall performance. Simultaneously, the photocatalytic carbon dioxide reduction reaction involves multiple conversion pathways and complex product distributions (such as methane, methanol, carbon monoxide, and formic acid), and the catalyst surface structure is relatively complex. Therefore, controlling product distribution and improving the selectivity of target products are key scientific issues determining the efficiency of carbon dioxide reduction. Summary of the Invention

[0004] To overcome the problems of existing technologies, this invention provides a cobalt-doped titanium dioxide photocatalyst, in which cobalt is highly dispersed in nano-titanium dioxide in an atomically dispersed form. Cobalt doping of titanium dioxide increases the number of surface active sites and accelerates charge transport, thereby improving the photocatalytic activity and CO selectivity of carbon dioxide.

[0005] The cobalt mentioned above is dispersed in nano-titanium dioxide in an atomically dispersed form, which means that the cobalt is dispersed in the form of single atoms.

[0006] According to one embodiment of the present invention, the loading of cobalt on titanium dioxide is 0.5wt%-8wt%.

[0007] Another object of the present invention is to provide a method for preparing the above-mentioned photocatalyst, comprising the following steps:

[0008] S1. Preparation of hydroxyl titanium precursor: Weigh the titanium source precursor and mix it with the solvent, then react it with a solvothermal agent to obtain the hydroxyl titanium precursor;

[0009] The titanium source precursor refers to a titanate ester, preferably at least one of tetrabutyl titanate or isopropyl titanate.

[0010] The technical solution of the present invention uses titanate ester as titanium source precursor, which has a higher CO2 reduction rate compared with other titanium source precursors, such as TiCl4.

[0011] S2. The titanium hydroxyl precursor obtained in step S1 is immersed in a cobalt salt precursor solution and dried to obtain a solid sample.

[0012] Cobalt atoms are anchored at specific sites by hydroxyl groups in the hydroxyl titanium precursor, and then highly dispersed in the titanium dioxide lattice framework through subsequent processing.

[0013] S3. The solid sample obtained in step S2 is calcined to obtain the cobalt-doped titanium dioxide photocatalyst.

[0014] The catalyst structure was directionally controlled by the above in-situ synthesis method, resulting in a uniform structure of surface active sites and high CO selectivity.

[0015] According to one embodiment of the present invention, in step S1, the solvent is an alcohol; preferably one or more of ethanol, glycerol, and isopropanol; more preferably a mixture of ethanol and glycerol.

[0016] The solvent system does not contain water, and its CO2 reduction rate is higher compared to solutions containing water.

[0017] According to one embodiment of the present invention, in step S1, the solvothermal reaction temperature is 180℃-300℃, and the solvothermal reaction time is 24-48 hours. The cooling method is furnace cooling or water cooling.

[0018] According to one embodiment of the present invention, in step S2, the cobalt salt precursor is one or more of cobalt chloride, cobalt nitrate, cobalt acetate, and cobalt sulfate.

[0019] According to one embodiment of the present invention, in step S3, the calcination temperature is 450℃-650℃, and the calcination time is 4h-12h. The heating rate is 1℃ to 10℃ per minute.

[0020] According to one embodiment of the present invention, in step S3, the roasting atmosphere is air.

[0021] Another object of the present invention is to provide the application of the above-described catalyst or the catalyst prepared by the above-described preparation method in photocatalytic CO2 reduction.

[0022] According to one embodiment of the present invention, the step of photocatalytic CO2 reduction includes: adding the photocatalyst to a photocatalytic reaction system containing carbon dioxide and water, wherein the main product obtained is CO and the selectivity is greater than 90%.

[0023] Beneficial effects:

[0024] Compared with the prior art, the advantages of the present invention are as follows:

[0025] 1. A cobalt source is introduced during the growth of the titanium dioxide lattice, and subsequent treatment induces its uniform distribution within the titanium dioxide lattice framework. The synthesis method is simple and requires no additional template or inducing agent. Simultaneously, the hydroxyl groups in the titanium hydroxyl precursor can be used to anchor cobalt atoms at specific sites during the synthesis process, directly controlling the electronic and chemical structure of the doped atoms.

[0026] 2. By introducing metal doping, the number of surface active sites is increased while the carrier density of the semiconductor itself is improved. At the same time, the light absorption performance can be controlled by the doping energy level, which can overcome the problem of severe carrier recombination in titanium dioxide single semiconductor. Furthermore, due to the enhanced light absorption performance and the increase of active sites, the activity and stability of photocatalytic carbon dioxide reduction can be greatly improved.

[0027] 3. The catalyst structure can be directionally controlled by in-situ synthesis to make its surface active site structure uniform and the product selectivity high.

[0028] The present invention will be further described below with reference to the accompanying drawings and specific embodiments. Attached Figure Description

[0029] Appendix Figure 1 This is the X-ray diffraction (XRD) pattern of titanium dioxide before and after cobalt doping.

[0030] Appendix Figure 2 This is a transmission electron microscope (TEM) image of the cobalt / titanium dioxide composite material.

[0031] Appendix Figure 3 This is a high-resolution aberration-corrected transmission electron microscope (AC-HRTEM) image of the cobalt / titanium dioxide composite material. Detailed Implementation

[0032] The technical solution of the present invention will be further described below with reference to specific embodiments. The scope of protection of the present invention is not limited to the following embodiments; these embodiments are listed for illustrative purposes only and do not limit the present invention in any way.

[0033] In the context of this specification, except where expressly stated, any matters or issues not mentioned herein are directly applicable to matters known in the art without any modification. Furthermore, any implementation described herein can be freely combined with one or more other implementations described herein, and any resulting technical solutions or concepts shall be considered part of the original disclosure or original record of this invention, and should not be regarded as new content not disclosed or anticipated herein, unless those skilled in the art consider such combination to be clearly unreasonable.

[0034] Photocatalytic carbon dioxide reduction applications

[0035] The obtained catalyst was used to simulate the photocatalytic reduction of CO2 under sunlight. Activity testing was conducted using an online vacuum photocatalytic reactor with a 300W xenon lamp as the light source. The reaction conditions were: 0.1g catalyst, 1ml water, and after three vacuum cycles, high-purity CO2 gas was introduced to bring the pressure inside the reactor to 0.08MPa. After the reaction started, samples were taken every hour, and the products were analyzed using a gas chromatograph equipped with a flame ionization detector and a thermal conductivity detector. Quantification was performed using a pre-determined standard curve. Three products were generated: CH4, CO, and H2.

[0036] Example 1:

[0037] 1 g of isopropyl titanate precursor, 50 mL of ethanol, and 30 mL of glycerol were weighed and thoroughly mixed, then transferred to a polytetrafluoroethylene-lined hydrothermal reactor. The mixture was hydrothermally reacted at 200 °C for 24 hours. After cooling in the furnace, the product was thoroughly washed with water and ethanol, and then vacuum dried at 40 °C for 24 hours to obtain the hydroxyl titanium precursor. 0.2 g of cobalt nitrate was weighed into 20 mL of water, and 2 g of the hydroxyl titanium precursor was added and stirred until homogeneous. The mixture was dried and then calcined in air at 550 °C for 2 hours. After cooling to room temperature, cobalt-doped titanium dioxide powder was obtained. (Appendix) Figure 1 The images show the XRD patterns of titanium dioxide doped with cobalt (a and b represent titanium dioxide and cobalt-doped titanium dioxide, respectively). It can be seen that the doping did not affect the structure of titanium dioxide itself, and the cobalt was highly dispersed. Figure 2 This is a TEM image of the cobalt / titanium dioxide composite material, showing that the sample particle size is uniformly distributed between 8-15 nm. (Attached) Figure 3 The image shows a high-resolution aberration-corrected transmission electron microscope image of the cobalt / titanium dioxide composite material, revealing that cobalt is dispersed in single-atom form within the titanium dioxide lattice framework. As shown in Appendix Table 1, Example 1 exhibited excellent photocatalytic carbon dioxide reduction activity, with corresponding CO and CH4 generation rates reaching 30.0 μmol g⁻¹. -1 h -1 and 2.0 μmol g -1 h -1 The CO selectivity reached 93.7%.

[0038] Example 2:

[0039] 1 g of isopropyl titanate precursor, 50 mL of ethanol, and 30 mL of glycerol were weighed and thoroughly mixed, then transferred to a polytetrafluoroethylene-lined hydrothermal reactor. The mixture was hydrothermally reacted at 200 °C for 48 hours. After cooling in the furnace, the product was thoroughly washed with water and ethanol and vacuum dried at 40 °C for 24 hours to obtain the hydroxyl titanium precursor. 0.2 g of cobalt acetate was weighed into 20 mL of water, and 2 g of the hydroxyl titanium precursor was added and stirred until homogeneous. The mixture was dried and calcined in air at 600 °C for 2 hours. After cooling to room temperature, cobalt-doped titanium dioxide powder was obtained. As shown in Appendix Table 1, its CO and CH4 generation rates in the photocatalytic carbon dioxide reduction test were 41.6 μmol g, respectively. -1 h -1 and 2.2 μmol g -1 h -1 The CO selectivity reached 95.0%.

[0040] Example 3:

[0041] 1 g of tetrabutyl titanate precursor, 50 mL of ethanol, and 20 mL of glycerol were weighed and thoroughly mixed, then transferred to a polytetrafluoroethylene-lined hydrothermal reactor. The mixture was hydrothermally reacted at 200 °C for 48 hours. After cooling with the furnace, the product was thoroughly washed with water and ethanol and vacuum dried at 40 °C for 24 hours to obtain the hydroxyl titanium precursor. 0.2 g of cobalt nitrate was weighed into 20 mL of water, and 2 g of the hydroxyl titanium precursor was added and stirred until homogeneous. The mixture was dried and calcined in air at 550 °C for 2 hours. After cooling to room temperature, cobalt-doped titanium dioxide powder was obtained. As shown in Appendix Table 1, its CO and CH4 generation rates in the photocatalytic carbon dioxide reduction test were 52.9 μmol g⁻¹. -1 h -1 and 2.1 μmol g -1 h -1 The CO selectivity reached 96.2%.

[0042] Example 4:

[0043] 1 g of tetrabutyl titanate precursor, 50 mL of ethanol, and 20 mL of glycerol were weighed and thoroughly mixed, then transferred to a polytetrafluoroethylene-lined hydrothermal reactor. The mixture was hydrothermally reacted at 180 °C for 48 hours. After cooling with the furnace, the product was thoroughly washed with water and ethanol and vacuum dried at 40 °C for 24 hours to obtain the hydroxyl titanium precursor. 0.2 g of cobalt sulfate was weighed into 20 mL of water, and 2 g of the hydroxyl titanium precursor was added and stirred until homogeneous. The mixture was dried and calcined in air at 500 °C for 2 hours. After cooling to room temperature, cobalt-doped titanium dioxide powder was obtained. As shown in Appendix Table 1, its CO and CH4 generation rates in the photocatalytic carbon dioxide reduction test were 75.6 μmol g, respectively. -1 h -1 and 3.1 μmol g -1 h-1 The CO selectivity reached 96.1%.

[0044] Example 5:

[0045] 2g of tetrabutyl titanate precursor, 50mL of ethanol, and 20mL of glycerol were weighed and thoroughly mixed, then transferred to a polytetrafluoroethylene-lined hydrothermal reactor. The mixture was hydrothermally reacted at 180℃ for 48 hours. After cooling with the furnace, the product was thoroughly washed with water and ethanol and vacuum dried at 40℃ for 24 hours to obtain hydroxyl titanium precursor. 0.2g of cobalt sulfate was weighed into 20mL of water, and 2g of hydroxyl titanium precursor was added and stirred until homogeneous. The mixture was dried and calcined in air at 500℃ for 2 hours. After cooling to room temperature, cobalt-doped titanium dioxide powder was obtained. As shown in Appendix Table 1, its CO and CH4 generation rates in the photocatalytic carbon dioxide reduction test were 55.2 μmol g, respectively. -1 h -1 and 2.0 μmol g -1 h -1 The CO selectivity reached 96.5%.

[0046] Furthermore, comparative experiments confirmed that the synergistic effect of cobalt-doped titanium dioxide plays a crucial role in enhancing the photocatalytic activity for carbon dioxide reduction. The specific scheme is as follows:

[0047] Comparative Example 1:

[0048] 1 g of isopropyl titanate precursor, 50 mL of ethanol, and 30 mL of glycerol were weighed and thoroughly mixed, then transferred to a polytetrafluoroethylene-lined hydrothermal reactor. The mixture was hydrothermally reacted at 200 °C for 24 hours. After cooling with the furnace, the product was thoroughly washed with water and ethanol, and vacuum dried at 40 °C for 24 hours to obtain hydroxyl titanium precursor. This precursor was then calcined at 500 °C in air for 2 hours and cooled to room temperature to obtain titanium dioxide powder. 0.2 g of cobalt nitrate was weighed into 20 mL of water, and 2 g of titanium dioxide was added and stirred until homogeneous. The mixture was dried and then calcined at 550 °C in air for 2 hours at a heating rate of 1 °C per minute. After cooling to room temperature, cobalt-loaded titanium dioxide powder was obtained. As shown in Appendix Table 1, the CO and CH4 generation rates in the photocatalytic carbon dioxide reduction test were 10.2 μmol g⁻¹. -1 h -1 and 3.2 μmol g -1 h -1 The CO selectivity was 76.1%.

[0049] Comparative Example 2:

[0050] Other conditions were the same as in Example 1, except that the solvent was replaced with water. As shown in Appendix Table 1, the CO and CH4 generation rates in the photocatalytic carbon dioxide reduction test were 17.2 μmol g.-1 h -1 and 6.4 μmol g -1 h -1 The CO selectivity was 72.9%.

[0051] Comparative Example 3:

[0052] Other conditions were the same as in Example 1, except that the titanium source was replaced with TiCl4. As shown in Appendix Table 1, the CO and CH4 generation rates in the photocatalytic carbon dioxide reduction test were 18.4 μmol g. -1 h -1 and 4.6 μmol g -1 h -1 The CO selectivity was 80.0%.

[0053] Table 1 Summary of Results

[0054]

[0055] As can be seen from the data in Table 1, introducing a cobalt source, using an alcohol solvent, and employing a titanate precursor during the titanium dioxide lattice growth process can effectively improve the CO generation rate and CO selectivity in photocatalytic CO2 reduction.

Claims

1. The application of a cobalt-doped titanium dioxide photocatalyst in the photocatalytic reduction of CO2 to CO and CH4, characterized in that, In the cobalt-doped titanium dioxide photocatalyst, cobalt is dispersed in nano-titanium dioxide in an atomically dispersed manner. The loading of cobalt on titanium dioxide is 0.5 wt%-8 wt%; The preparation method of the cobalt-doped titanium dioxide photocatalyst includes the following steps: S1. Preparation of hydroxyl titanium precursor: Weigh the titanium source precursor and mix it with the solvent, and then obtain the hydroxyl titanium precursor through a solvothermal reaction; the titanium source precursor is a titanate precursor, and the solvent is one or more of ethanol, glycerol, and isopropanol, and no water is added to the solvent system. S2. The titanium hydroxyl precursor obtained in step S1 is immersed in a cobalt salt precursor solution and dried to obtain a solid sample. S3. The solid sample obtained in step S2 is calcined to obtain the cobalt-doped titanium dioxide photocatalyst. In step S1, the solvothermal reaction temperature is 180℃-300℃ and the solvothermal reaction time is 24-48 hours.

2. The application according to claim 1, characterized in that, The solvent is a mixture of ethanol and glycerol.

3. The application according to claim 1, characterized in that, In step S1, the solvothermal reaction temperature is 180-200℃.

4. The application according to claim 1, characterized in that, In step S2, the cobalt salt precursor is one or more of cobalt chloride, cobalt nitrate, cobalt acetate, and cobalt sulfate.

5. The application according to claim 1, characterized in that, In step S3, the calcination temperature is 450℃-650℃, and the calcination time is 4 h-12 h.

6. The application according to claim 1, characterized in that, In step S3, the roasting atmosphere is air.

Citation Information

Patent Citations

  • Gold atom / titanium dioxide composite material as well as preparation method and application thereof

    CN111151246A